Growth optimization of potassium solubilizing bacteria isolated from biofertilizer - Ahmad Azinuddin, Zakaria (2009)
Potassium is one of the essential nutrients for plant to growth and required in large amount to achieve optimum growth. Biofertilizer is a good platform to deliver this primary macronutrient by assistance of Potassium Solubilizing Bacteria (KSB). To acquire the optimum outcome by applying this bacterium into the biofertilizer, the optimum growth condition must be studied. The optimum growth conditions for KSB based on temperature, pH and initial glucose concentration parameters were studied during this research. The Design of Experiment (DOE) software was used to design the optimization experimental work and analyse the results produced. The range for these three parameters were set at 25°C - 32°C, pH 6 - pH 8 and 8g/L - 13 g/L respectively. The fermentation was run for 72 hours at 200rpm of agitation rate in incubator shaker. Two responses were studied during fermentation process which were cell number and glucose consumption. The fermentation process was run in 250 mL shake flasks. Bacteria’s cell concentration was determined by using colony forming unit (CFU) method. On the other hand, glucose consumption was measured by using DNS method. All the results were transferred into the DOE software for analysis process. Within the stated range, the software suggested that the optimum growth condition for Potassium Solubilizing Bacteria is at temperature of 32°C, pH 8 and with 8g/L initial glucose concentration.